Longitudinal manipulation of the kinematic chain using a reducing biofeedback schedule - Mulloy, F.; Mullineaux, D. R.; Irwin, G. (ISBS Proceedings Archive (Michigan), 2017)
Feedback has been shown to be an influential component in skill development, yet this has not been assessed longitudinally in a complex motor skill. Novices (n=32) were introduced to a lunge touch task. Visual biofeedback were given on the timing and magnitude of rear leg kinematics. Results showed that those who received feedback adapted their movement patterns by developing extension velocity magnitudes (40.0%, 24.8% and 28.9% increases for the hip, knee and ankle respectively). The changes were retained across 26 weeks, with a reducing visit schedule of feedback. These results demonstrate that knowledge of performance based biofeedback interventions alone are effective in developing whole limb contributions in an explosive task, and that a reducing visit schedule negates dependence on feedback.